2020
DOI: 10.24093/awej/vol11no1.29
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Implementing Reciprocal Teaching in L2 Classes on Female Students' Perception of their Reading Skills and Motivation to Read

Abstract: This study aimed to investigate the effectiveness of reciprocal teaching (RT) in improving high school female students' attitudes toward reading in a second language as the results might shed light on effective teaching practices in the L2 classrooms. To this end, a self-report questionnaire was developed and validated by the researcher. A quasi-experimental design was used, whereby the study sample was divided into two groups, experimental and control. The experimental group was taught reading in English clas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Considering that the mother tongue creates an essential part of the learner's environment, it is the fundamental basis for developing verbal skills (Van Wyk & Mostert, 2016). On the other side, Qutob (2020) indicates that the lack of awareness of the difference between the mother tongue and second or foreign language in terms of linguistic system makes learning writing and speaking skills more difficult for learners. This lack of awareness of different characteristics and features is likely to confuse the EFL students, leading them to fall back on their L1 to imitate some of its features and structures and employ them in L2 writing.…”
Section: Definition Of Terminologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that the mother tongue creates an essential part of the learner's environment, it is the fundamental basis for developing verbal skills (Van Wyk & Mostert, 2016). On the other side, Qutob (2020) indicates that the lack of awareness of the difference between the mother tongue and second or foreign language in terms of linguistic system makes learning writing and speaking skills more difficult for learners. This lack of awareness of different characteristics and features is likely to confuse the EFL students, leading them to fall back on their L1 to imitate some of its features and structures and employ them in L2 writing.…”
Section: Definition Of Terminologiesmentioning
confidence: 99%
“…Palestinian learners usually change the stylistic features of their first language; Arabic, to the target language; English, as Abu Rass's (2015) indicated. For these reasons, Arabic speakers face specific challenges in English learning (Qutob, 2020). Many students indicated that Arabic is an essential language to their studies because most of their modules or subjects are taught in Arabic.…”
Section: Section One: What Are the Challenges That Efl Students' Face...mentioning
confidence: 99%